Cysteamine broadly improves the anti-plasmodial activity of artemisinins against murine blood stage and cerebral malaria. (December 2016) - Moradin, Neda; Torre, Sabrina; Gauthier, Susan; Tam, Mifong; Hawari, Jalal; Vandercruyssen, Kirsten; De Spiegeleer, Bart; Fortin, Anny; Stevenson, Mary; Gros, Philippe
Abstract Background The potential emergence and spread of resistance to artemisinins in thePlasmodium falciparum malaria parasite constitutes a major global health threat. Hence, improving the efficacy of artemisinins and of artemisinin-based combination therapy (ACT) represents a major short-term goal in the global fight against malaria. Mice defective in the enzyme pantetheinase (Vnn3 ) show increased susceptibility to blood-stage malaria (increased parasitaemia, reduced survival), and supplementation ofVnn3 mutants with the reaction product of pantetheinase, cysteamine, corrects in part the malaria-susceptibility phenotype of the mutants. Cysteamine (Cys) is a small, naturally occurring amino-thiol that has very low toxicity in vivo and is approved for clinical use in the life-long treatment of the kidney disorder nephropathic cystinosis. Methods The ability of Cys to improve the anti-plasmodial activity of different clinically used artemisinins was tested. The effect of different CYS/ART combinations on malarial phenotypes (parasite blood-stage replication, overall and survival from lethal infection) was assessed in a series of in vivo experiments usingPlasmodium strains that induce either blood-stage (Plasmodium chabaudi AS) or cerebral disease (Plasmodium berghei ANKA). This was also evaluated in an ex vivo experimental protocol that directly assesses the effect of such drug combinations on the viability ofPlasmodium parasites, as measured by the ability of tested parasites to induce a productive infection in vivo in otherwise naïve animals. Results Cys is found to potentiate the anti-plasmodial activity of artesunate, artemether, and arteether, towards the blood-stage malaria parasiteP. chabaudi AS. Ex vivo experiments, indicate that potentiation of the anti-plasmodial activity of artemisinins by Cys is direct and does not require the presence of host factors. In addition, potentiation occurs at sub-optimal concentrations of artemisinins and Cys that on their own have little or no effect on parasite growth. Cys also dramatically enhances the efficacy and protective effect of artemisinins against cerebral malaria induced by infection with theP. berghei ANKA parasite. Conclusion These findings indicate that inclusion of Cys in current formulations of ACT, or its use as adjunct therapy could improve the anti-plasmodial activity of artemisinin, decrease mortality in cerebral malaria patients, and prevent or delay the development and spread of artemisinin resistance.